Strategic management for tourism communities bridging the gaps - Murphy Ann E; Murphy Peter E (New Delhi Viva Books, 2006)
Strategic planning within a community framework is essential for tourism to reach its potential. This book combines the four principal functions of business management and stakeholder analysis to develop a model of collaborative decision making. This mode
Keywords: Tourism; Tourism-management